Phalaenopsis Mite, Tenuipalpus pacificus Baker (Arachnida: Acari: Tenuipalpidae) - Harold A. Denmark (EDIS)
EENY-377, a 3-page illustrated fact sheet by H. A. Denmark, is part of the Featured Creatures collection. It describes the distribution, description, biology, hosts, economic importance and management of this destructive pest of greenhouse orchids. Includes selected references. Published by the UF Department of Entomology and Nematology, October 2006.